Kemas Ulang Informasi Perpustakaan Berbasis Animasi Digital - Sutarsyah Sutarsyah (Jurnal IPI (Ikatan Pustakawan Indonesia), 2022)
Animation-based visual media is an option in repackaging information in the library because visual media is more attractive than text. This paper describes the creation of animated film digital content in the Bogor Botanical Gardens Library. The content or materials are made based on publications of the Bogor Botanical Gardens, historical places, and environmental phenomena around the library. Making animation aims to optimize the use of books and library facilities. The method steps used are identification of collections, phenomena, and user behavior in the library. Animated films made by the Bogor Botanical Gardens Library show representations of libraries, book collections, clippings and environmental phenomena around which will add insight to users. There are 8 films made from 2013-2019 that were uploaded on Youtube with the keyword "Film Animasi Perpustakaan Kebun Raya Bogor". The animated films that were made: 1). Kantong Semar: Ayo Banyak Tahu dengan Membaca Buku di Perpustakaan, 2). Yuk Mengenal Buah Langka di Kebun Raya Bogor, 3). Yuk ke Perpustakaan: Pengenalan Koleksi Biji Terbang, (4). Perpustakaan Kebun Raya Bogor: Makam Belanda di Kebun Raya Bogor), 5) Perpustakaan Sumber Ilmu, Banyak Baca Banyak Tahu, 6) Serunya di Perpustakaan: Ngobrol dengan Buku, 7) Perbedaan Amorphophallus titanum dan Rafflesia patma, and 8) Manfaat Kelelawar bagi Penyebaran Tanaman. The animated films produced is grouped into 6 aspects as follows: 1) information on library facilities and services, 2) introduction to guest books and electronic catalogs, 3) friendliness of librarian, 4) storytelling, 5) introduction to library collections, and 6) introduction to plants, animals and places history in the Bogor Botanical Gardens.